2006
DOI: 10.1017/s0305000906007550
|View full text |Cite
|
Sign up to set email alerts
|

From scalar semantics to implicature: children's interpretation of aspectuals

Abstract: One of the tasks of language learning is the discovery of the intricate division of labour between the lexical-semantic content of an expression and the pragmatic inferences the expression can be used to convey. Here we investigate experimentally the development of the semantics–pragmatics interface, focusing on Greek-speaking five-year-olds' interpretation of aspectual expressions such as arxizo (‘start’) and degree modifiers such as miso (‘half’) and mexri ti mesi (‘halfway’). Such expressions are known to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 44 publications
(63 reference statements)
3
36
0
3
Order By: Relevance
“…We argue that children's interpretation of indefinites reflects a pragmatic failure to derive a scalar implicature. Our conclusion supports an established line of acquisition research on scalar implicatures for a new domain of language (Chierchia et al, 2004;Noveck, 2001;Papafragou, 2006;Pouscoulous et al, 2007).…”
Section: Asupporting
confidence: 89%
“…We argue that children's interpretation of indefinites reflects a pragmatic failure to derive a scalar implicature. Our conclusion supports an established line of acquisition research on scalar implicatures for a new domain of language (Chierchia et al, 2004;Noveck, 2001;Papafragou, 2006;Pouscoulous et al, 2007).…”
Section: Asupporting
confidence: 89%
“…Another possibility is that this failure is due to the demands imposed by the experimental task on an otherwise pragmatically savvy child." (p. 261) However, it is possible to be more specific in a way that can distinguish computations that are general to all implicatures from those that are specific to quantifiers (for example, see Tantalou & Papafragou, 2004;Papafragou, 2006). The evidence from Wynn (1990) indicates that children's problem is not related to augmentation based on scale mates, since children apparently do augment when interpreting numerals that they have not yet mastered.…”
Section: Informative Boundaries To Implicaturementioning
confidence: 99%
“…Given this training, children were significantly more likely to compute implicatures relative to conditions that lacked training. This indicates that children can augment expressions when it is clearly required in a context, and when they have been prompted to generate scalar alternatives (see also Tantalou &Papafragou, 2004, andPapafragou, 2006;see Musolino, 2004, for evidence that 5-year-olds can access "at least" and "at most" interpretations for numerals when favored contextually).…”
Section: Informative Boundaries To Implicaturementioning
confidence: 99%
“…This difficulty has often been attributed to an underdeveloped processing ability or pragmatic competence (see Musolino 2006;Musolino & Lidz 2006;Papafragou 2006;Papafragou & Musolino 2003;Papafragou & Tantalou 2004;Pouscoulous, Noveck, Politzer & Bastide 2007). This paper explores an alternative hypothesis that children fail to compute scalar implicatures because they lack knowledge of the relevant scalar alternatives to words like some (see Barner & Bachrach 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested various factors that might affect children's derivation of implicatures, including limitations on working memory, limited understanding of context and meta-linguistic tasks, and the salience or availability of relevant scalar alternatives (see Chierchia et al 2001;Musolino 2006;Musolino & Lidz 2006;Papafragou 2006;Papafragou & Musolino 2003;Papafragou & Tantalou, 2002;Pouscoulous et al 2007). According to Papafragou and Musolino, since each of these factors might limit children's computation of implicatures, and since children readily assign exact interpretations to numerals, children must not be using implicatures to derive exact meanings of numerals.…”
Section: Introductionmentioning
confidence: 99%